PERANCANGAN VIRTUAL ASSISTANT ENTREPRENEURSHIP MENGGUNAKAN METODE SCRUM - Sudaryono Sudaryono; Nuke Puji Lestari; Ketut Gunawan (LPPM Unbaja, 2020)
The birth of technology which until now is increasingly developing in all fields makes human work easier. Where services in the field of e-commerce and entrepreneurship can get information from a technology. However, there has been no development of a service information system for beginner entrepreneurs in obtaining information about entrepreneurship. So, the purpose of this research is the presence of a Virtual Assistant by building a chatbot to provide information to entrepreneurs through data that is already stored on the website system. In addition, experienced entrepreneurs can share information on the system. This design produces a chatbot prototype using AIML (Artificial Intelligence Markup Language) translated by ALICE (Artificial Linguistic Internet Computer Entity). This AIML function is so that the Chatbot is able to integrate the input results received in the form of text input so as to produce a conversation between the user and the program. The use of chatbots that are equipped with various information in the form of audio makes it easier for users to get information from a database system that is informed to prospective entrepreneurs. The Agile SDLC development method with the Scrum framework in this study helps system planning to run smoothly and is adjusted to the presence of artificial intelligence which makes entrepreneurs meet the information in starting the right business. The end result of this research, the system is able to motivate entrepreneurs, get information from an entrepreneur forum, and other tutorials about entrepreneurship.